Could there be an association between chronic brucellosis and endothelial damage? - Turhan Togan; Ozgur Ciftci; Hale Turan; Huseyin Narci; Hakan Gullu; Hande Arslan (Journal of Infection in Developing Countries)
Introduction: In this study, we examined the effects of Brucella infection on endothelial dysfunction. Flow-mediated dilatation (FMD) measurement is indicator of the endothelial function, and abnormal values indicating endothelial dysfunction are accepted as the first stage of atherosclerosis. Methodology: Twenty-four patients who had been treated for acute brucellosis two years before, and who had had no relapses in the follow-up, were prospectively included in the study, along with 30 healthy individuals in the control group. Results: While the highly sensitive C-reactive protein (hs-CRP) value was 2.42 ± 1.45 in the patient group, it was 1.72 ± 0.61 in the control group (p = 0.025). While the FMD value was 3.50 ± 1.58 in the patient group, it was 5.88 ± 1.88 in the control group (p < 0.001). While the percentage increase in FMD was 9.88 ± 4.92 in the patient group, it was 17.49 ± 6.3 in the control group (p < 0.001). It was observed that FMD value, the percentage increase in FMD, and basal radius were correlated with hs-CRP (r = -0.644, p < 0.001; r = - 0.558, p = 0.002; r = 0.444, p = 0.018, respectively). The carotid artery intima media thickness (IMT) value was found to be 0.61 ± 0.17 in the patient group and 0.49 ± 0.12 in the control group (p = 0.004). Conclusions: The abnormal FMD and IMT values observed in brucellosis patients might be an indicator of more frequent arterial dysfunction, increased cardiovascular risk, and atherosclerosis.